Internalisasi Pendidikan Nilai Kemandirian dan Moderasi di Pesantren Sunan Drajat Lamongan - Ulum, Miftachul; Mun’im, Abdul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
Pondok Pesantren and scientific networks cannot be separated from the role of a kiai. A scientific network based on spiritual factors makes Pondok Pesantren and kiai role models for society. This research aims to describe the education of the values of independence and moderation at the Pondok Pesantren Sunan Drajat Lamongan. The focus of this research is the process of instilling educational values of independence and moderation which is still ongoing at the Pondok Pesantren Sunan Drajat Lamongan. Sources of informants include caregivers, family caregivers, students, Pondok Pesantren administrators, foundation administrators, dormitory administrators, informal institution administrators, formal institution administrators, regional organization administrators, alumni and the surrounding community. The results of the research show that instilling educational values of independence and moderation starts from habituation activities carried out in daily life at Pondok Pesantren. Instilling the values of independence and moderation begins with increasing awareness and vigilance in social life in the Pondok Pesantren environment